2022
DOI: 10.3390/su14052951
|View full text |Cite
|
Sign up to set email alerts
|

Mediation and Online Learning: Systematic Literature Mapping (2015–2020)

Abstract: Mediation is a crucial element in the learning process, especially in a virtual environment, whether it corresponds to formal, non-formal, or informal education. This paper aims to expose the research on mediation and learning in virtual environments published between 2015 and 2020. A total of 299 articles were identified that address the topic of mediation and learning in virtual environments from different fields and approaches. The results that respond to the research questions are presented. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…These competitions are mainly reflected in the level of comprehensive national strength and talents. The key to talent construction is reflected in the comprehensive quality level [1,2]. English ability is an important part of the comprehensive quality training of talents in colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…These competitions are mainly reflected in the level of comprehensive national strength and talents. The key to talent construction is reflected in the comprehensive quality level [1,2]. English ability is an important part of the comprehensive quality training of talents in colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there is very little research on the relation between learning environment (regarding factors of course content, learning activities and class relationship), self-efficacy and SRL. Systematic literature review by Riofrío-Calderón and Ramírez-Montoya (2022) showed that the topic of mediation in online learning is novel and suggested strengthening future research related to elements of educational process such as contents, materials or interaction. Therefore, this study intends to test the mediation effect of self-efficacy on the relation between learning environment and SRL, with the environment consisting of course design, learning activities and relationship in class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Confronted with these changes, educational institutions have to adapt rapidly to let their learners to acquire and develop skills in, with, and for digital technologies that are necessary for the new societal challenges [5]. Consequently, many schools at all levels have been prompted to include a number of technological resources that endorse the teaching-learning process through the use of innovative pedagogical approaches.…”
Section: Introductionmentioning
confidence: 99%